The Nexus of servant leadership, employee loyalty, and job satisfaction - Rice Furinika; Raniasari Bimanti Esthi; Indra Setiawan (Faculty of Economics and Business Mulawarman University, 2023)
This research aims to learn how servant leadership influences workers' commitment to their jobs at PT. Sinar Utama Mandiri. Sixty workers were surveyed for this quantitative investigation using Saturated sampling. Data processing software, SmartPLS (Partial Least Square) Version 4.0, performs analyses such as validity, reliability, and hypothesis testing, as well as the design and analysis of path outer models and inner models. The results showed no significant relationship between servant leadership and employee loyalty, as measured by t-statistics for the variable job satisfaction PT Sinar Utama Mandiri, which equaled 2.417, indicating a substantial relationship between servant leadership and job satisfaction. Therefore, PT. Sinar Utama Mandiri's employees are more loyal when their boss serves them well and when they are happy in their jobs.